Особенности течения беременности, родов, послеродового периода, состояния новорожденных у женщин с пиелонефритом - Ляшенко, Е.Н.; Заболотнов, В.А.; Рыбалка, А.Н.; Боева, О.И.; Кадырова, З.М. (Таврический медико-биологический вестник, 2011)
У статті наведені сучасні дані про пієлонефрит у вагітних. Описані особливості перебігу вагітності,
пологів, післяпологового періоду, стану новонароджених у жінок з пієлонефритом. The modern findings about pyelonephritis at the pregnant women are presented in given article. The
features of the course of the pregnancy, the labor, the postpartum stage, the condition of the newborn babies
in the women with pyelonephritis are described.